High-performance uv glue for ito film and preparation method and application thereof

CN121628557BActive Publication Date: 2026-10-23SHANGHAI CHEM-LAND IND CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511859010.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-12-10
Publication Date
2026-10-23
Estimated Expiration
2045-12-10

AI Technical Summary

Technical Problem

[0004]为了解决现有UV胶的耐候性、附着力、耐黄变性能无法兼顾的技术难题,本发明提供了一种用于ITO膜的高性能UV胶及其制备方法和应用,聚氨酯丙烯酸酯或者聚氨酯丙烯酸酯+环氧丙烯酸酯作为主体树脂(以下简称成膜树脂)配合兼具刚性结构和柔性结构的丙烯酸酯单体(以下简称稀释单体)平衡胶层固化之后的柔韧性和耐磨性,又利用硅烷偶联剂作为附着力促进剂,使网状结构连接成三维结构提升整体的物化性能,赋予UV胶高耐候性、高耐黄变性、长效附着力,更好满足ITO镀层产品的胶粘需求

Benefits of technology

1、本发明提供的UV胶具有高耐候性、高耐黄变性、长效附着力的优点,且形成的胶膜表面光滑,光泽度高,适合作为ITO膜表面高性能UV胶使用。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present application relates to the field of UV optical adhesive, and particularly relates to a high-performance UV adhesive for ITO film, a preparation method and application thereof.A high-performance UV adhesive for ITO film comprises the following raw materials in parts by weight: 35-55 parts of modified acrylate oligomer, 15-35 parts of active diluent monomer, 3-5 parts of photoinitiator composition, 0.5-3 parts of defoaming agent, 0.5-3 parts of wetting agent, 0.5-3 parts of leveling agent, and 0.5-3 parts of adhesion promoter; the modified acrylate oligomer is polyurethane acrylate; or the modified acrylate oligomer is formed by compounding polyurethane acrylate and epoxy acrylate.The UV adhesive provided by the present application has excellent properties of high weather resistance, high yellowing resistance and long-term adhesion, and the adhesive film formed has a smooth surface and high gloss, and is suitable for use as a high-weather-resistance UV adhesive for the surface of ITO film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of UV optical adhesives, and more particularly to a high-performance UV adhesive for ITO films. Background Technology

[0002] Traditional UV adhesives generally do not have high requirements for water resistance and high temperature resistance. To create higher-performance products, a higher resin content is needed, requiring the addition of large amounts of solvent for dilution and ease of application. Therefore, a dual-curing process, i.e., "heat + UV," must be used during curing. This method has two significant drawbacks: first, because it contains solvents, heat is required to remove them, consuming a large amount of electricity; second, the solvents evaporate into the air, causing environmental pollution. To avoid these problems and meet national environmental protection requirements, solvent-free UV adhesives have emerged.

[0003] In the field of ITO films, due to the need for extended ITO coating performance and protection, the UV adhesives used must at least meet the requirements of high weather resistance and long-lasting adhesion. Furthermore, during the use of ITO films, the adhesive film formed by the UV adhesive serves as the base film, upon which other materials are bonded. Therefore, the UV adhesive must possess sufficient adhesion to meet the high strength requirements during use, prevent adhesive layer peeling, and protect the substrate. Finally, when ITO films are applied in the optical display field, the yellowing resistance of the UV adhesive is particularly important. However, existing UV adhesives, in order to meet adhesion requirements, often contain a high content of benzene ring structures in their formulation, which leads to poor yellowing resistance. Therefore, this invention provides a high-performance UV adhesive for ITO films, its preparation method, and its applications. Summary of the Invention

[0004] To address the technical challenge of existing UV adhesives failing to simultaneously achieve optimal weather resistance, adhesion, and yellowing resistance, this invention provides a high-performance UV adhesive for ITO films, along with its preparation method and application. Polyurethane acrylate or a mixture of polyurethane acrylate and epoxy acrylate serves as the main resin (hereinafter referred to as the film-forming resin), combined with acrylate monomers possessing both rigid and flexible structures (hereinafter referred to as diluent monomers) to balance the flexibility and abrasion resistance of the cured adhesive layer. Furthermore, a silane coupling agent is used as an adhesion promoter, connecting the network structure into a three-dimensional structure to enhance the overall physicochemical properties. This results in a UV adhesive with high weather resistance, high yellowing resistance, and long-lasting adhesion, better meeting the adhesive requirements of ITO coated products.

[0005] The present invention provides a high-performance UV adhesive for ITO films, which is achieved through the following technical solution: A high-performance UV adhesive for ITO films is made from the following raw materials in parts by weight: 35-55 parts of modified acrylate oligomer, 15-35 parts of reactive diluent monomer, 3-5 parts of photoinitiator composition, 0.5-3 parts of defoamer, 0.5-3 parts of wetting agent, 0.5-3 parts of leveling agent, and 0.5-3 parts of adhesion promoter; wherein the modified acrylate oligomer is polyurethane acrylate; or the modified acrylate oligomer is formed by compounding polyurethane acrylate and epoxy acrylate.

[0006] The UV adhesive provided by this invention has the advantages of high weather resistance, high yellowing resistance, and long-lasting adhesion. The resulting adhesive film has a smooth surface and high gloss, making it suitable for use as a high-performance UV adhesive for ITO film surfaces.

[0007] Preferably, the polyurethane acrylate is any one of SD871, SD2001, SD1002B, SD7539B, SD1216H, and SD8602 from Guangzhou Songda New Material Technology Co., Ltd., or any one of CR91517, CR92402, CR91191, and CR93013 from Guangdong Haohui New Material Co., Ltd.; the epoxy acrylate is any one of EBECRYL 248, EBECRYL 3708, EBECRYL 3702, EBECRYL 3701, and EBECRYL 3700 from Zhanxin Resin (China) Co., Ltd., or CR90426 from Guangdong Haohui New Material Co., Ltd.

[0008] Preferably, the reactive diluent monomer is at least one selected from tert-butylcyclohexyl acrylate, dicyclopentenyl acrylate, tetrahydrofuran acrylate, isobornyl acrylate, methyl isobornyl acrylate, trimethylolpropane triacrylate, dipropylene glycol diacrylate, and 1,6-hexanediol diacrylate.

[0009] Preferably, the photoinitiator composition is at least one of photoinitiator 184, photoinitiator 1173, photoinitiator 2959, photoinitiator 907, photoinitiator ITX, photoinitiator EDB, and photoinitiator DETX.

[0010] Preferably, the adhesion promoter is an aminosilane or an aminosilane oligomer; the aminosilane is at least one selected from KH-550, KH-540, KH-902, KH-553, KH-554, KH-590, KH-602, KH-703, KH-792, KH-892, KH-170, KH-270, KH-620, and KH-793; the aminosilane oligomer is formed by reacting at least one selected from KH-550, KH-540, KH-902, KH-553, KH-554, KH-590, KH-602, KH-703, KH-792, KH-892, KH-170, KH-270, KH-620, and KH-793.

[0011] Preferably, the wetting agent is at least one of BYKJET 9151, EBECRIL 436, TEGO Dispers 689, BASF WE 3322, BASF Hydropalat WE3650, BYK-UV 3505, BYK-UV 3510, BYK-UV 3511, and BYK-UV 3530.

[0012] Preferably, the leveling agent is at least one of BASF Rheovis HS 1332, Rheovis PU1191, Rheovis PU1291, BYK 1788, BYK-361N, and BYK-331.

[0013] Preferably, the defoamer is at least one of BASF FoamStar SI 2293, FoamStar SI2292, TEGO Airex 944, TEGO Airex 96, BYK 1790, and BYK 1794.

[0014] The present invention provides a method for preparing a high-performance UV adhesive for ITO films, which is achieved through the following technical solution: A method for preparing a high-performance UV adhesive for ITO films includes the following steps: Under a UV-free environment, accurately measured modified acrylate oligomers and reactive diluent monomers are placed in a mixing tank, heated to 50-60°C, and mixed for 15-30 minutes with stirring at 200-500 rpm. After the modified acrylate oligomers are completely dissolved, accurately measured photoinitiator composition, defoamer, wetting agent, leveling agent, and adhesion promoter are added to the mixing tank. After all components are added, the stirring speed is adjusted to 400-600 rpm, and the mixture is stirred for 15-30 minutes. The resulting filtrate is the high-performance UV adhesive for ITO films. The present invention provides a method for preparing a high-performance UV adhesive for ITO films. The preparation method is simple, requires little skill from technicians, and is easy to prepare and produce quickly.

[0015] The high-performance UV adhesive for ITO films provided in this invention is used in the field of optical display ITO films. The UV curing conditions of the high-performance UV adhesive are as follows: UV curing under a high-pressure mercury lamp, the main wavelength of the high-pressure mercury lamp is 365nm, the unit light energy A is 25~35mW / cm², the exposure time B is 60±5s, and the cumulative light energy A*B is 1500-2000mJ / cm².

[0016] In summary, the present invention has the following advantages: 1. The UV adhesive provided by this invention has the advantages of high weather resistance, high yellowing resistance, and long-lasting adhesion. The resulting adhesive film has a smooth surface and high gloss, making it suitable for use as a high-performance UV adhesive for ITO film surfaces.

[0017] 2. The preparation method of the present invention is relatively simple, has low operation difficulty, and is easy to achieve efficient configuration and production. Detailed Implementation

[0018] To further understand the inventiveness and technical advancements of this invention, the preferred embodiments of this invention will be discussed in detail below with reference to examples and comparative examples.

[0019] Example: A high-performance UV adhesive for ITO films is made of 35-55 parts of modified acrylate oligomer, 15-35 parts of reactive diluent monomer, 3-5 parts of photoinitiator composition, 0.5-3 parts of defoamer, 0.5-3 parts of wetting agent, 0.5-3 parts of leveling agent, and 0.5-3 parts of adhesion promoter.

[0020] The modified acrylate oligomer is a polyurethane acrylate; or the modified acrylate oligomer is formed by compounding polyurethane acrylate and epoxy acrylate.

[0021] The polyurethane acrylate is any one of SD871, SD2001, SD1002B, SD7539B, SD1216H, and SD8602 from Guangzhou Songda New Material Technology Co., Ltd., or any one of CR91517, CR92402, CR91191, and CR93013 from Guangdong Haohui New Material Co., Ltd.

[0022] The epoxy acrylate is any one of EBECRYL 248, EBECRYL 3708, EBECRYL 3702, EBECRYL 3701, and EBECRYL 3700 from Zhanxin Resins (China) Co., Ltd., or CR90426 from Guangdong Haohui New Materials Co., Ltd.

[0023] The reactive diluent monomer is at least one of tert-butylcyclohexyl acrylate, dicyclopentenyl acrylate, tetrahydrofuran acrylate, isobornyl acrylate, methyl isobornyl acrylate, trimethylolpropane triacrylate, dipropylene glycol diacrylate, and 1,6-hexanediol diacrylate.

[0024] The photoinitiator composition is at least one selected from photoinitiator 184, photoinitiator 1173, photoinitiator 2959, photoinitiator 907, photoinitiator ITX, photoinitiator EDB, and photoinitiator DETX. Preferably, the photoinitiator composition is photoinitiator 184.

[0025] The adhesion promoter is an aminosilane or an aminosilane oligomer.

[0026] The aminosilane is at least one of KH-550, KH-540, KH-902, KH-553, KH-554, KH-590, KH-602, KH-703, KH-792, KH-892, KH-170, KH-270, KH-620, and KH-793.

[0027] The aminosilane oligomers are formed by reacting at least one of KH-550, KH-540, KH-902, KH-553, KH-554, KH-590, KH-602, KH-703, KH-792, KH-892, KH-170, KH-270, KH-620, and KH-793.

[0028] The wetting agent is at least one of BYKJET 9151, EBECRIL 436, TEGO Dispers 689, BASF WE 3322, BASF Hydropalat WE 3650, BYK-UV 3505, BYK-UV 3510, BYK-UV 3511, and BYK-UV 3530.

[0029] The leveling agent is at least one of BASF Rheovis HS 1332, Rheovis PU 1191, Rheovis PU 1291, BYK1788, BYK-361N, and BYK-331.

[0030] The defoamer is at least one of BASF FoamStar SI 2293, FoamStar SI 2292, TEGO Airex 944, TEGO Airex 96, BYK1790, and BYK1794.

[0031] A method for preparing a high-performance UV adhesive for ITO films includes the following steps: Under UV-free conditions, accurately measured modified acrylate oligomers and reactive diluent monomers are placed in a mixing tank, heated to 50-60°C, and mixed for 15-30 minutes with stirring at 200-500 rpm. After the modified acrylate oligomers are completely dissolved, accurately measured photoinitiator compositions, defoamers, wetting agents, leveling agents, and adhesion promoters are added to the mixing tank. After all components are added, the stirring is stopped. Adjust the stirring speed to 400-600 rpm, stir for 15-30 minutes, and then filter the filtrate. The resulting filtrate is the high-performance UV adhesive for ITO films. The prepared high-performance UV adhesive is used in the field of optical display ITO films. Its UV curing conditions are as follows: UV curing under a high-pressure mercury lamp, with a main wavelength of 365 nm, a unit light energy A of 25~35 mW / cm², an exposure time B of 60±5 s, and a cumulative light energy A*B of 1500-2000 mJ / cm².

[0032] ITO film coating process: Before coating, the ITO film is wiped with anhydrous ethanol. After the surface is dry, the prepared high-performance UV adhesive for ITO film is applied by hand. The high-performance UV adhesive for ITO film is heated to 40-50℃ before use. The ambient temperature for coating is 23±1℃ and the relative humidity is 50±10%. After coating, it is placed under a high-pressure mercury lamp for UV curing. The unit light energy A is 25~35mW / cm², the exposure time B is 60±5s, and the cumulative light energy A*B is 1500-2000mJ / cm², which can form a dry film thickness of 10-20μm on the ITO film.

[0033] Example 1: A high-performance UV adhesive formulation for ITO films is as follows: 15g of epoxy acrylate EBECRYL 248, 35g of polyurethane acrylate SD871, 15g of tetrahydrofuran acrylate, 25g of isobornyl acrylate, 2.4g of photoinitiator 184, 1.6g of photoinitiator TPO, 3g of adhesion promoter KH550, 0.5g of defoamer BYK1794, 2g of compound wetting agent, and 0.5g of compound leveling agent. The compound wetting agent is composed of BYK-UV 3511 and EBECRYL 436 in a mass ratio of 0.5:2. The compound leveling agent is composed of BYK-361N and BYK 1788 in a mass ratio of 1:1.

[0034] A method for preparing a high-performance UV adhesive for ITO films includes the following steps: Under a light-protected environment, 15g of epoxy acrylate EBECRYL 248 and 35g of polyurethane acrylate SD871 are placed in a glass beaker, sealed with aluminum foil, and placed on a magnetic stirrer with heating function. The temperature is raised to 55°C, and the mixture is stirred at 300 rpm for 20 minutes. After the modified acrylate oligomer is completely dissolved, 15g of tetrahydrofuran acrylate, 25g of isobornyl acrylate, 2.4g of photoinitiator 184, 1.6g of photoinitiator TPO, 3g of adhesion promoter KH550, 0.5g of defoamer BYK1794, 2g of compound wetting agent, and 0.5g of compound leveling agent are added to the glass beaker. After all the ingredients are added, the stirring speed is 500 rpm, and the mixture is stirred for 20 minutes. The mixture is then filtered through 200-mesh gauze. The filtrate is the high-performance UV adhesive for ITO films.

[0035] ITO film coating process: Before coating, the ITO film is wiped with anhydrous ethanol. After the surface is dry, the prepared high-performance UV adhesive for ITO film is applied by hand. The high-performance UV adhesive for ITO film is heated to 45℃ before use. The ambient temperature for coating is 23±1℃ and the relative humidity is 50±10%. After coating, it is placed under a high-pressure mercury lamp for UV curing. The unit light energy A is 30mW / cm², the exposure time B is 60s, and the cumulative light energy A*B is 1800mJ / cm², which can form a dry film thickness of 15μm on the ITO film.

[0036] The difference between Example 2 and Example 1 is as follows: A high-performance UV adhesive for ITO films is formulated as follows: 5g of epoxy acrylate EBECRYL 248, 45g of polyurethane acrylate SD871, 30g of isobornyl acrylate, 2.4g of photoinitiator 184, 1.6g of photoinitiator TPO, 3g of adhesion promoter KH550, 0.5g of defoamer BYK1794, 2g of compound wetting agent, and 0.5g of compound leveling agent. The compound wetting agent is composed of BYK-UV 3511 and EBECRYL 436 in a mass ratio of 0.5:2. The compound leveling agent is composed of BYK-361N and BYK 1788 in a mass ratio of 1:1.

[0037] The difference between Example 3 and Example 1 is as follows: A high-performance UV adhesive for ITO films is formulated as follows: 10g of epoxy acrylate CR90426, 30g of polyurethane acrylate CR92402, 28g of dicyclopentenyl acrylate DCPA, 22g of isobornyl acrylate, 3g of photoinitiator 184, 2g of photoinitiator TPO, 1g of adhesion promoter KH550, 0.5g of defoamer BYK1794, 1g of compound wetting agent, and 0.5g of compound leveling agent. The compound wetting agent is composed of BYK-UV 3511 and EBECRYL 436 in a mass ratio of 0.5:2. The compound leveling agent is composed of BYK-361N and BYK 1788 in a mass ratio of 1:1.

[0038] The difference between Example 4 and Example 3 is that the formulation of a high-performance UV adhesive for ITO films is as follows: 10g of polyurethane acrylate CR93013, 30g of polyurethane acrylate SD8602, 28g of dicyclopentenyl acrylate DCPA, 22g of isobornyl acrylate, 3g of photoinitiator 184, 2g of photoinitiator TPO, 1g of adhesion promoter KH550, 0.5g of defoamer BYK1794, 1g of compound wetting agent, and 0.5g of compound leveling agent. The compound wetting agent is composed of BYK-UV 3511 and EBECRYL 436 in a mass ratio of 0.5:2. The compound leveling agent is composed of BYK-361N and BYK 1788 in a mass ratio of 1:1.

[0039] The difference between Comparative Example 1 and Example 1 is that in the formulation of the high-performance UV adhesive for ITO film, 2.4g of photoinitiator 184 and 1.6g of photoinitiator TPO were adjusted to 1.6g of photoinitiator 184 and 1.2g of photoinitiator TPO, while the other components remained unchanged. The difference between Comparative Example 2 and Example 2 is that the high-performance UV adhesive for ITO film does not contain adhesion promoter KH550.

[0040] The difference between Comparative Example 3 and Example 3 is that no compound wetting agent is added to the formulation of the high-performance UV adhesive used for ITO film.

[0041] The difference between Comparative Example 4 and Example 4 is that no compound wetting agent is added to the formulation of the high-performance UV adhesive used for ITO film.

[0042] Performance test 1: Initial adhesion was measured according to AST D3359.

[0043] Performance test 2: Water boiling aging performance test. The sample was placed in boiling water and boiled for 2.0 hours. After being cooled to room temperature, the adhesion after boiling in boiling water for 2 hours was measured by AST D3359.

[0044] Performance Test 3: Resistance to Damp Heat Cycling. The test standard is based on GB / T 1740-2007 "Determination of Resistance to Damp Heat of Coating Film". This standard specifies that the test chamber temperature is 47±1℃, the humidity is 96%±2%, and the test is conducted continuously for 48 hours, followed by a check every 72 hours after two checks, for a total test time of 240 hours (48h / 48h / 72h / 72h). After each check, the board should be moved. After the 240-hour test, the board is removed from the test chamber and cooled to room temperature, and the adhesion is measured according to AST D3359.

[0045] Performance test 4: According to HG / T 0004-2012, the sample was placed in a high and low temperature aging test chamber for high and low temperature impact test. The low temperature was -40℃ for 30 min, the high temperature was 85℃ for 30 min, the temperature conversion time was 5 min, and the cycle was repeated 1000 times. After cooling to room temperature, the adhesion was measured according to AST D3359.

[0046] Performance test 5: According to GB / T 1771-2007 "Determination of resistance to neutral salt spray of paints and varnishes", the sample was placed in a salt spray aging test chamber. The test conditions were: temperature 35±2°C, sodium chloride solution concentration 5%, pH value 6.5-7.2. After 72 hours of testing, the sample was taken out and cooled to room temperature. The adhesion was then measured according to AST D3359.

[0047] Performance test 6: Double 85 aging test (THB). The sample was placed in the double 85 aging test chamber and aged at 85℃ / 85%RH for 1000h. After being taken out and cooled to room temperature, the adhesion was measured according to AST D3359.

[0048] Performance Test 7: Yellowing Resistance. According to GB / T 11186.3-1989 "Methods for Measurement of Coating Color - Part 3: Calculation of Color Difference", the Lab* values ​​E1 and E2 of the color difference of the samples before and after the double 85 aging test are measured using a spectrophotometer (color difference ΔE = |E1 - E2|, required to be less than 1.5), and visual evaluation is performed under a standard light source (D65 light source). Before testing, the equipment must be calibrated using a black and white calibration plate, and the average value of multiple points should be taken to ensure accuracy.

[0049] Table 1: Test parameters of UV adhesives in Examples 1-4 and Comparative Examples 1-4 Table 2: Test parameters of UV adhesives in Examples 1-4 and Comparative Examples 1-4 Based on Examples 1-4 and Comparative Examples 1-4, and in conjunction with Table 1-2, it can be seen that Examples 1-4 met the requirements in all tests. Notably, after undergoing various aging tests, all performance characteristics remained unchanged from before aging. This indicates that the adhesive has very high stability, and that the UV adhesive provided in this invention, after UV curing, forms a film with excellent properties such as high weather resistance, high resistance to yellowing, and long-lasting adhesion.

[0050] As can be seen from Example 1 and Comparative Example 1, and Tables 1-2, Comparative Example 1 suffered from insufficient long-wavelength light-induced dosage, resulting in poor coating curing. Water molecules could easily penetrate the uncured adhesive from the surface and remain for a long time, causing it to fail the water resistance, damp heat cycling, and aging tests.

[0051] Combining Example 2 and Comparative Example 2 with Tables 1-2, it can be seen that in Comparative Example 2, without the addition of an adhesion promoter, although the bottom adhesive could cure normally, the adhesion between the adhesive layer and the substrate was insufficient, resulting in poor adhesion. Methacryloxy-based adhesion promoters contain C=C double bonds, which can further participate in the cross-linking curing reaction. Because no adhesion promoter was added, the resin and monomers struggled to form a high-strength three-dimensional spatial structure, resulting in large gaps between the one-dimensional resin chains and the two-dimensional resin network, allowing water molecules to easily penetrate the adhesive layer. These two points caused Comparative Example 2 to fail most tests.

[0052] Based on Examples 3-4 and Comparative Examples 1-4 and Table 1-2, it can be seen that no wetting agent was added in Comparative Examples 3 and 4, which resulted in the inability to form a continuous, flat, and smooth coating after curing. Therefore, moisture could penetrate into the adhesive layer from a location with poor leveling, resulting in a situation where, although most aging tests passed, the coating was still worse than that of Examples 3 and 4 compared to Comparative Examples 1, 2, and 3.

[0053] In summary, the UV adhesive provided in this invention forms an adhesive film after UV curing, which has excellent properties such as high weather resistance, high yellowing resistance, and long-lasting adhesion. Moreover, the surface of the adhesive film is smooth and has high gloss, making it suitable for use as a high weather-resistant UV adhesive for ITO film surfaces.

[0054] It should be noted that this specific embodiment is merely an explanation of the technical solution of the present invention and is not intended to limit the present invention. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but as long as they are within the scope of the claims of the present invention, they are protected by patent law.

Claims

1. A high-performance UV adhesive for ITO films, characterized in that: it is It is made from the following raw materials in parts by weight: 15g of epoxy acrylate EBECRYL 248, 35g of polyurethane acrylate SD871, 15g of tetrahydrofuran acrylate, 25g of isobornyl acrylate, 2.4g of photoinitiator 184, 1.6g of photoinitiator TPO, 3g of adhesion promoter KH550, 0.5g of defoamer BYK1794, 2g of compound wetting agent, and 0.5g of compound leveling agent; the compound wetting agent is composed of BYK-UV 3511 and EBECRYL436 in a mass ratio of 0.5:2; the compound leveling agent is composed of BYK-361N and BYK 1788 in a mass ratio of 1:

1.

2. The high-performance UV adhesive for ITO films according to claim 1, characterized in that: The preparation method of the high-performance UV adhesive for ITO films includes the following steps: Under a light-protected environment, 15g of epoxy acrylate EBECRYL248 and 35g of polyurethane acrylate SD871 are placed in a glass beaker, sealed with aluminum foil, placed on a magnetic stirrer with heating function, heated to 55°C, and mixed for 20 minutes under stirring at 300 rpm until the epoxy acrylate EBECRYL248...

248. After the polyurethane acrylate SD871 is completely dissolved, add 15g tetrahydrofuran acrylate, 25g isobornyl acrylate, 2.4g photoinitiator 184, 1.6g photoinitiator TPO, 3g adhesion promoter KH550, 0.5g defoamer BYK1794, 2g compound wetting agent, and 0.5g compound leveling agent to a glass beaker. After all the ingredients are added, stir at 500 rpm for 20 minutes. Then filter through 200-mesh gauze. The filtrate is the high-performance UV adhesive for ITO films.

3. The high-performance UV adhesive for ITO films according to claim 1, characterized in that: The application process of the high-performance UV adhesive for ITO film is as follows: Before applying the adhesive, the ITO film is wiped with anhydrous ethanol. After the surface is dry, the prepared high-performance UV adhesive for ITO film is applied by hand. The high-performance UV adhesive for ITO film is heated to 40-50℃ before use. The ambient temperature for application is 23±1℃ and the relative humidity is 50±10%. After the adhesive is applied, it is cured under a high-pressure mercury lamp. The unit light energy A is 25~35mW / cm², the exposure time B is 60±5s, and the cumulative light energy A*B is 1500-2000mJ / cm², which can form an adhesive film with a dry film thickness of 10-20μm on the ITO film.

4. A high-performance UV adhesive for ITO films, characterized in that: it is It is made from the following raw materials in parts by weight: 5g of epoxy acrylate EBECRYL 248, 45g of polyurethane acrylate SD871, 30g of isoborneol acrylate, 2.4g of photoinitiator 184, 1.6g of photoinitiator TPO, 3g of adhesion promoter KH550, 0.5g of defoamer BYK1794, 2g of compound wetting agent, and 0.5g of compound leveling agent; the compound wetting agent is composed of BYK-UV 3511 and EBECRYL 436 in a mass ratio of 0.5:2; the compound leveling agent is composed of BYK-361N and BYK 1788 in a mass ratio of 1:

1.

5. A high-performance UV adhesive for ITO films, characterized in that: it is It is made from the following raw materials in parts by weight: 10g of epoxy acrylate CR90426, 30g of polyurethane acrylate CR92402, 28g of dicyclopentenyl acrylate DCPA, 22g of isobornyl acrylate, 3g of photoinitiator 184, 2g of photoinitiator TPO, 1g of adhesion promoter KH550, 0.5g of defoamer BYK1794, 1g of compound wetting agent, and 0.5g of compound leveling agent; the compound wetting agent is composed of BYK-UV 3511 and EBECRYL 436 in a mass ratio of 0.5:2; the compound leveling agent is composed of BYK-361N and BYK 1788 in a mass ratio of 1:

1.

6. A high-performance UV adhesive for ITO films, characterized in that: It is made from the following raw materials in parts by weight: 10g of polyurethane acrylate CR93013, 30g of polyurethane acrylate SD8602, 28g of dicyclopentenyl acrylate DCPA, 22g of isobornyl acrylate, 3g of photoinitiator 184, 2g of photoinitiator TPO, 1g of adhesion promoter KH550, 0.5g of defoamer BYK1794, 1g of compound wetting agent, and 0.5g of compound leveling agent; the compound wetting agent is composed of BYK-UV 3511 and EBECRYL 436 in a mass ratio of 0.5:2; the compound leveling agent is composed of BYK-361N and BYK 1788 in a mass ratio of 1:1.

Citation Information

Patent Citations

  • UV glue and preparation method thereof

    CN106833497A

  • Sealing compound and preparation method and application thereof

    CN106916537A